Pemahaman MUI Dan Implementasinya Tentang Akad Mudarabah Pada Bank Syariah Indonesia Di Tabagsel - Dame Siregar; Fauzi Rizal; Sawaluddin Siregar Siregar; Neila Hifhzi Siregar (Journal of Economic, Bussines and Accounting (COSTING), 2023)
All the arguments that forbid mudarabah contracts in BSI, are still general meanings, can still be compromised with other arguments that are not forbidden. The mudarabah contract has many arguments that justify it, including QS al-Baqoroh, 275, -283 and the hadith narrated by Ibn Majah number 2331 and narrated by ad-Darimi number 2940. Supporting verses are verses related to the hasan qordon (QS al-Baqoroh 2:245, al-Maidah 5:12, al-Hadid 57:11 and 18, at- Tagobun 64:17, al-Muzzammil, 73:20. If a deed has more benefits than harm, it is halal. The lawfulness of lending is not the loan contract but the reason for mutual consent, mutual benefit, the data may eat first in the shop and then pay. The marriage contract is a pillar of marriage, the purpose of which is to make it lawful to have sexual intercourse with one's spouse. The permissibility of mudarabah contracts in terms of general issues, if there are right and wrong actions in the action, but more good than wrong, the law is halal, and can maintain the objectives of maqosyidusy sayriah (QS al-Baqoroh 2: 219) and added to the hadith which contains no harm and harm between sohibul mal and BSI and customers. Keywords: Mudarabah Agreement, BSI, MUI Tabagsel